Racial Differences in the Association Between Alcohol Drinking and Cigarette Smoking: Preliminary Findings From an Alcohol Research Program. (4th June 2021) - Harris, Julia C; Mereish, Ethan H; Faulkner, Monica L; Assari, Shervin; Choi, Kelvin; Leggio, Lorenzo; Farokhnia, Mehdi
Abstract: Aims: Important differences have been shown in alcohol drinking and cigarette smoking prevalence, patterns and consequences among individuals from different racial backgrounds. Alcohol and nicotine are often co-used, and the association between drinking and smoking may differ between racial groups—a question explored in the present study. Methods: Data from the NIAAA natural history and screening protocols were utilized; non-Hispanic Black and non-Hispanic White individuals were included in the analyses [ N  = 1692; 65.2% male; 58.3% met criteria for current alcohol use disorder (AUD); 37.8% were current cigarette smokers]. Bivariate associations between assessments related to alcohol drinking and cigarette smoking were examined, and the strength and direction of these associations were compared between the two groups. Results: The sample included 796 Black and 896 White individuals. Black participants had higher frequency ( P  < 0.0001) and severity ( P  = 0.007) of AUD, as well as higher frequency ( P  < 0.0001) of cigarette smoking. Bivariate analyses showed that the expected positive associations between alcohol drinking and cigarette smoking, observed among White individuals, were blunted or absent among Black individuals [age at first cigarette—AUD identification test (AUDIT) score: F (1, 292) = 7.60, P  = 0.006; cigarette pack years—AUDIT score: F (1, 1111) = 10.97, P  = 0.001]. Conclusions: Some decoupling in the association between alcohol drinking and cigarette smoking was found among Black compared to White individuals. The sample was drawn from a specific population enrolled in alcohol research protocols, which is a limitation of the present study. These preliminary findings highlight the importance of considering racial/ethnic background in preventive and therapeutic strategies for comorbid alcohol and nicotine use. Abstract : Short Summary: This study investigated differential association between alcohol drinking andcigarette smoking across non-Hispanic Black and White participants of analcohol research program. Results found decoupling in the drinking–smoking link among Black versus White individuals, highlighting theimportance of considering racial/ethnic background in substance useresearch and treatment.